WORKSHOP AND ASSESSMENT ASSISTANCE FOR TEACHER GUIDANCE AND COUNSELING FOR JUNIOR HIGH SCHOOL SUKOHARJO REGENCY - Adi Dewantoro; Marifatin Indah Kholili (Study Program Guidance and Counseling, Univesitas Pendidik, 2021)
The purpose of this community service is to provide assistance and assessment training for guidance and counseling teachers at the junior high school level in Sukoharjo Regency. The implementation method used is In-service training 1 (in class)-offline-On the job training (OJT)-In-service Training (In class) 2 offline, abbreviated as In1-OJT-In2 training model. In-1 offline mode activities include concept exposure activities, OJT activities include the implementation of assessments, presentations, discussions, In2 activities include evaluation and reflection. It is hoped that after this service program is carried out, guidance and counseling teachers have knowledge and insight related to guidance and counseling assessments so that they can improve guidance and counseling services even better.